U(2) Lie Algebraic Study of Vibrational Spectra of Fullerene C80 and Its Epoxide C80–O - Sen, R.; Kalyan, A.; Paul, R.S.; Das, R.; Choudhury, J.; Sarkar, N.K.; Bhattacharjee, R. (Ukrainian Journal of Physics, 2012)
Using the Lie algebraic method, the stretching vibrational energies of fullerene C80 & its epoxide C80–O are calculated in the one-dimensional U(2) framework. By constructing the model Hamiltonian with the help of Casimir and Majorana invariant operators in this framework, we calculated the local mode vibrational energy levels of fullerene C80 & C80–O.